Foraging ecology of shorebirds at Buntal and Sambir, Sarawak - Aminah, binti Imat. (Universiti Malaysia Sarawak (UNIMAS), 2006)
A study of foraging ecology of shorebirds was done in Buntal and Sambir beach. This study was carried out by doing observation of shorebirds and collecting the mudflat samples from three different distance of water edge. The mudflat samples were divided into three layers of depth that are less than 5 cm, 5-10 cm and 10-15 cm. A total of 1137 bird observation frequency from 27 species representing four families had been observed and recorded from both study sites. In total, four taxic classes of benthic organisms viz polychaetes, malacostraca, bivalves and gastropods were recorded from both mudflat ecosystem. The statistical analysis indicates that there is no correlation between number of birds and food availability at Sambir while at Buntal the correlation is significant.